Space, sonic trajectories and the perception of cadence in electroacoustic music. Issue 3 (27th May 2021) - Danieli, Luca; Witek, Maria; Haworth, Christopher
Abstract : This paper reports on an exploratory study in the field of electroacoustic music aimed at understanding whether a sensation similar to that associated with the concept of "cadence" in relation to tonal music can be identified when listening to sounds diffused in space. Using a variety of patterned stimuli in a perceptual experiment, we asked listeners to evaluate the completeness of multiple trajectories on the horizontal plane. The results show differences across multiple categories of listeners, and suggest that listeners acquainted with spatial music consider trajectories more complete when presenting the last two impulses at opposite directions from the centre.